2020
DOI: 10.1097/mpg.0000000000002957
|View full text |Cite
|
Sign up to set email alerts
|

Proton‐pump Inhibitor Response Prediction Using Esophageal microRNAs in Children With Eosinophilic Esophagitis

Abstract: Objectives: Eosinophilic esophagitis (EoE) is a chronic esophageal disease characterized by eosinophilic inflammation. Proton-pump inhibitors (PPI) induce disease remission but no predictive factors of PPI-responsiveness have been identified yet. So, a biomarker must be found to differentiate between responders (PPI-R) and nonresponder patients (PPI-NR) to PPI. Aims were to identify any molecular biomarker that could predict PPI responsiveness and to study molecular remission after PPI therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 34 publications
0
16
0
2
Order By: Relevance
“…We can hypothesize that PPI-responsive patients have an epithelial barrier dysfunction possibly mediated by estrogen-responsive genes, thus making males more prevalent in this group. Further studies analyzing the different molecular expression profiles of PPI responders and non-responders may help to further elucidate these clinical observations (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…We can hypothesize that PPI-responsive patients have an epithelial barrier dysfunction possibly mediated by estrogen-responsive genes, thus making males more prevalent in this group. Further studies analyzing the different molecular expression profiles of PPI responders and non-responders may help to further elucidate these clinical observations (40,41).…”
Section: Discussionmentioning
confidence: 99%
“… 127 In a separate study, Cañas et al have identified several microRNAs in esophageal biopsy tissue that may discriminate between PPI responders and non-responders at baseline. 207 …”
Section: The Future: Ppi Precision Medicine For Eoementioning
confidence: 99%
“…Likewise, significant upregulation of serum miR-21 30-fold in EoE correlated with an increased expression 40-fold in the esophageal tissue [ 19 ]. Unfortunately, there is still little evidence of circulating microRNAs in EoE, and other authors failed when they tried to detect them in the serum [ 168 ]. Differences in mRNAs have also been explored as potential circulating biomarkers for EoE [ 169 , 170 , 171 ].…”
Section: Current Knowledge Of Circulating Biomarkersmentioning
confidence: 99%